To use the Zero Power Rule, we first need to evaluate the expression \( -2 + 10 \).
Calculating this, we get: \[ -2 + 10 = 8 \]
Now, substituting this back into the original expression \( 43(-2 + 10) \): \[ 43(-2 + 10) = 43(8) \]
Next, we can express the constant term \( 43 \) multiplied by \( 8 \): \[ 43 \cdot 8 = 344 \]
Using the Zero Power Rule (which states that any non-zero number raised to the power of zero is equal to \( 1 \)), we can also express \( 344 \) as: \[ 344 = 43 \cdot (8) = 43(-2+10) \]
So, the equivalent expression to \( 43(-2 + 10) \) is: \[ 43(8) \]
Therefore, you can fill in the blank as: An equivalent expression to 43(−2+10) is 43(8).